Servizi Sociali Territoriali e Università: Esempi di Sinergie Possibili per un Percorso di Qualità - Laura Bini (Social Work & Society, 2007)
Although - or because - social work education in Italy has for some 15 years now been exclusively in the domain of the university the relationship between the academic world and that of practice has been highly tenuous. Research is indeed being conducted by universities, but rarely on issues that are of immediate practice relevance. This means that forms of practice develop and become established habitually which are not checked against rigorous standards of research and that the creation of knowledge at academic level pays scant attention to the practice implications of social changes. This situation has been made even worse by the dwindling resources both in social services and at the level of the universities which means that bureaucratic procedures or imports of specialisations from other disciplines frequently dominate the development of practice instead of a theory-based approach to methodology. This development does not do justice to the actual requirements of Italian society faced with ever increasing post-modern complexity which is reflected also in the nature of social problems because it implies a continuation of a faith in modernity with its idea of technical, clear-cut solutions while social relations have decidedly moved beyond that belief. This discrepancy puts even greater strain on the personnel of welfare agencies and does ultimately not satisfy the ever increasing demands for quality and accountability of services on the part of users and the general public. Social workers badly lack fundamental theoretical reference points which could guide them in their difficult work to arrive at autonomous, situation-specific methodological answers not based on procedures but on analytical knowledge. Thirty years ago, in 1977, a Presidential Decree created the legal basis for the establishment of social service departments at the level of municipalities which created opportunities for the direct involvement of the community in the fight against exclusion. For this potential to be fully utilized it would have required the bringing together of three dimensions, the organizational structure, the opportunities for learning and research in the territory and the contribution by the professional community. As this did not occur social services in Italy still often retain the character of charity which does not concern itself with the actual causes of poverty and exclusion. This in turn affects the relationship with citizens in general who cannot develop trust in those services. Through uncritical processes of interaction Edgar Morin's dictum manifests itself which is that without resorting to critical reflection on complexity interventions can often have an effect that totally the opposite to the original intention. An important element in setting up a dynamic interchange between academia and practice is the placement on professional social work courses. Here the looping of theory to practice and back to theory etc. can actually take place under the right organizational and conceptual conditions, more so than in abstract, and for practitioners often useless debates about the theory-practice connection. Furthermore, research projects at the University of Florence Social Work Department for instance aim at fostering theoretical reflection at the level of and with the involvement of municipal social service agencies. With a general constructive disposition towards research and some financial investment students were facilitated to undertake social service practice related research for their degree theses for instance in the city of Pistoia. In this way it was also possible to strengthen the confidence and professional identity of social workers as they became aware of the contribution their own discipline can make to practice-relevant research instead of having to move over to disciplines like psychology for those purposes. Examples of this fruitful collaboration were presented at a conference in Pistoia on 25 June 2007. One example is a thesis entitled 'The object of social work' and examines the difficult development of definitions of social work and comes to the conclusion that 'nothing is more practical than a theory'. Another is on coping abilities as a necessary precondition for the utilization of resources supplied by social services in exceptional circumstances. Others deal with the actual sequence of interventions in crisis situations, and one very interestingly looks at time and how it is being constructed often differently by professionals and clients. At the same time as this collaboration on research gathers momentum in the Toscana, supervision is also being demanded more forcefully as complementary to research and with the same aim of profiling more strongly the professional identity of social work. Collaboration between university and social service filed is for mutual benefit. At a time when professional practice is under threat of being defined from the outside through bureaucratic prescriptions a sound grounding in theory is a necessary precondition for competent practice.